Implementing a pharmacogenetic-driven algorithm to guide dual antiplatelet therapy (DAPT) in Caribbean Hispanics: protocol for a non-randomised clinical trial. Issue 8 (6th August 2020) - Hernandez-Suarez, Dagmar F; Melin, Kyle; Marin-Maldonado, Frances; Nunez, Hector J; Gonzalez, Ariel F; Gonzalez-Sepulveda, Lorena; Rivas-Tumanyan, Sona; Naik, Hetanshi; Ruaño, Gualberto; Scott, Stuart A; Duconge, Jorge
Abstract : Introduction: Minority populations in the USA are disproportionately affected by cardiovascular conditions. Reduced responsiveness to clopidogrel among carriers of CYP2C19 variants has been reported in patients with either coronary artery disease (CAD) or acute coronary syndrome (ACS) after the percutaneous coronary intervention (PCI). Previous studies have evaluated CYP2C19 genotyping-guided antiplatelet therapy in selected populations; however, this has yet to be tested among Hispanics. Given the paucity of clinical research on CYP2C19 and antiplatelet clinical outcomes in Hispanics, our study will test the safety and efficacy of a genetic-driven treatment algorithm to guide dual antiplatelet therapy (DAPT) in Caribbean Hispanics. Methods and analysis: This is a multicentre, prospective, non-randomised clinical trial that proposes an assessment of pharmacogenomic-guided DAPT in post-PCI Caribbean Hispanic patients with ACS or CAD. We will recruit 250 patients to be compared with a matched non-concurrent cohort of 250 clopidogrel-treated patients (standard-of-care). Major adverse cardiovascular events (MACEs) such as all-cause death, myocardial infarction (MI), stroke, coronary revascularisation, stent thrombosis and bleedings over 6 months will be the study endpoints. Among the recruited, high-risk patients will be escalated to ticagrelor and low-risk patients will remain on clopidogrel. The primary objective is to determine whether genetic-guided therapy is superior to standard of care. The secondary objective will determine if clopidogrel treatment in low-risk patients is not associated with a higher rate of MACEs compared with escalated antiplatelet therapy in high-risk patients. Patients will be enrolled up to the group's completion. Ethics and dissemination: Approval was obtained from the Institutional Review Board of the University of Puerto Rico Medical Sciences Campus (protocol # A4070417). The study will be carried out in compliance with the Declaration of Helsinki and International Conference on Harmonization Good Clinical Practice Guidelines. Findings will be published in a peer-reviewed journal and controlled access to experimental data will be available. Trial registration number: NCT03419325 ; Pre-results.